Reflecting on the use of community radio and performing arts for seeking accountability for those facing intersecting inequalities. (13th January 2020) - López Franco, E; Boham, B; Elyanu, J; Howard, J; Larweh, K; Quarmyne, W
Abstract: " Community Radio – a different kind of radio, we work with our people. Together we plan, together we decide; together we implement. We work with our people " (GCRN Community Radio Anthem) 1 . This practice-based article presents the experiences and reflections of two pioneer organizations which are continuously innovating with the use of community radio. We share reflections on its use as a tool for building inclusive communities that are able to seek accountability, especially for those facing intersecting inequalities deriving from identity-based as well as other social, economic and spatial drivers. These organizations are Radio Ada–based in the Greater Accra region in Ghana, founding member of the Ghana Community Radio Network (GCRN) and the Soroti Justice and Peace Commission (SOCAJAPIC) in North Eastern Uganda. Both organizations see community radio as central to their participatory practice, through which they articulate and promote the right to communicate as fundamental for inclusion and accountability 2 . They partnered with the Institute of Development Studies (IDS) in the UK to explore how participatory action research processes can contribute to building sustainable social inclusion and pathways to accountability for the most marginalized (see Shaw, Howard and López Franco (2020) Article in this issue). The article is primarily based on an interview with Wilna Quarmyne, Kofi Larweh, Ben Boham Okiror and John Elyanu, founding members and leaders of Radio Ada and SOCAJAPIC, respectively, but also draws on research data and from previous stages of work with both organizations as part of the Participate initiative's research on accountability for those most marginalized (Burns, Ikita, López Franco, Shahrokh, (2015) Citizen Participation and Accountability for Sustainable Development, IDS, Brighton; Howard, López Franco and Wheeler (2017) Participatory Monitoring and Accountability and the Sustainable Development Goals: A Learning Report of the Participate Network, Participate Network, Brighton. Find the full report at: https://opendocs.ids.ac.uk/opendocs/bitstream/handle/123456789/13326/Participate_LearningReport_Final.pdf?sequence=1&isAllowed=y ). Other reflective moments and dialogue, resulting through rounds of feedback to drafts of this article, have also shaped the outcome. The piece is organized in four sections in an aim to explain how community radio has been a key driver of accountability for populations confronting intersecting inequalities, through combining this with different expressions of participatory performing arts 3, simplified here as processes whereby " participants instigate and realise their own creative idea. They are the directors/curators of the piece. Professional artist/s are involved if it is the participants" decision to do so' (Tiller 2013 p11). The first section introduces the work of Radio Ada and SOCAJAPIC, explaining their approach to community radio, performing arts and social change, by each organization. Section 2 presents reflections on using radio as a means for shifting social norms in the quest for building inclusion. Section 3 speaks to the ways that community radio is being used to support multiple marginalized groups in seeking accountability. Section 4 presents some limitations and obstacles emerging for community radio stations to maintain their work towards sustained social change.